(untitled) (Fiep Bulletin - online, 2011)
INTRODUCTION: Bariatric surgery is the most effective treatment available for morbid obesity. Physical activity can contribute to better results in weight loss after bariatric surgery, while preserving lean body mass and decreasing changes in energy metabolism. One method to offset the negative effects on body composition due to sudden weight loss may be the Bodybuilding therapy, that is composed of sixteen patterns of movements (exercises), divided into sections of the upper part and lower limbs and abdomen. The range of heart rate during training should be between 60% to 85% of maximum heart rate (MHR), established by the Tanaka equation. Objective: To verify the effectiveness of therapy in individual Bodybuilding after bariatric surgery, and body composition by mass index (BMI), total body weight, percentage of lean body mass, body fat percentage and metabolic rate (BMR ) through a case study. Methods: this research involved an individual volunteer who underwent bariatric surgery, women with 30 years of age, sedentary. Was carried out in the pre and post therapy Bodybuilding, anthropometrical and body composition. The subject performed three sessions of Bodybuilding therapy a week for three months. Results: When comparing the periods before and after therapy were observed Bodybuilding decrease in total body weight, body fat and BMI, and there was an increase in lean body mass and RMR. Conclusion: Our data suggest that the positive contribution Bodybuilding therapy on body composition in post-bariatric surgery, demonstrated by an increase in lean body mass, maintenance of resting metabolic rate, and decreased body fat.